KALMAN FILTER FOR STATIC GNSS PRECISE POINT POSITIONING - Arif Muhammad (NIM : 15113033), Norman
Precise Point Positioning can offer an estimate of horizontal precision as good as 10 to 5 centimetre. This however, can only be reached by using appropriate means of estimation technique, data, and correction models. This research is aiming at establishing Kalman Filter-based algorithm with appropriate correction models to process GNSS observation data in order to obtain 10-centimetre level of horizontal position estimate. In this research however, horizontal precision at 0,204 metre and 1,856 metre is obtained while using static dynamic model and position-velocity dynamic model respectively. This result is due to unmodeled bias factors and high noise characteristic that is not yet considered.